Freedom of Transit: A right for transit traffic to move across borders? - Shumba, Willie (Border Crossing, 2025)
The world has become a global village, and various efforts have been made to facilitate trade, including transit traffic. In international trade, transit involves the movement of goods to the destination through third-party countries. Landlocked countries experience challenges in that they access trade with the rest of the world through seaports belonging to other territories. The freedom to transit through third party countries is therefore an important avenue that has gained traction in facilitating global trade. The freedom to transit is a concept that has evolved and improved over the years. This paper examines the efforts taken by international treaties to facilitate the movement of goods in transit: starting with the Barcelona Convention and Statute on Freedom of Transit of 1921, then the General Agreement on Tariffs and Trade, and lately, the Trade Facilitation Agreement of the World Trade Organisation. The paper analyses the progressive liberalisation of the transit regime over a century and brings out the impact that has been contributed to international trade. The study established that the Barcelona Convention on Transit provided the foundation, while Article V of GATT 1994 built upon that foundation. The Trade Facilitation Agreement represents the latest effort to facilitate traffic in transit.